Bisphosphonates Related Ocular Side Effects: A Case Series and Review of Literature. (17th November 2022) - Gendelman, Omer; Tripto - Shkolnik, Liana; Vered, Iris; Lidar, Merav
ABSTRACT: Objective: To describe the clinical features of patients with bisphosphonate related ocular side effects (BROSE). Methods: The medical records of all patients with BROSE between January 2009 and December 2019 were reviewed. Results: Nine cases with BROSE were identified. All subjects were female. Median age at diagnosis was of 69 years. The leading indication for bisphosphonate treatment was osteoporosis (n=7), Paget's disease of bone (n=1) and breast cancer (n=1). Six (66.67%) patients presented with uveitis, one (11%) episcleritis and two (22%) with orbital inflammation. Five events (55.5%) occurred within 10 days of initiating the bisphosphonate and the rest (44.44%) developed within 2 weeks to 3 years later. Four (44.44%) patients had concurrent thyroid disease. An association was found between underlying thyroid disease or autoimmunity. Conclusion: BROSE is an uncommon complication of bisphosphonate therapy occurring more frequently in patients with an autoimmune predisposition.